Formação de nitrato e nitrito e degradação protéica por processamento térmico de sardinha (triportheus angulatus) - (:unkn) unknown (Universidade Federal do Amazonas, 2010)
Fishing is an important extractive activity in the Amazon, and offering nutritional source income, leisure and food base of a large proportion of its population. His organic constitution, as well as other food matrices, under certain preparation conditions, such as baking, suffers physical and chemical changes, which may give rise to secondary products. The aim of this study was to analyze the formation of nitrates and nitrites (nitrosating compounds), which are important precursors of nitrous compounds from protein myofibrillar degradation caused by application of heat in samples of sardine (Triportheus angulatus) for 30 to 60 minutes. Being a methodology quick, simple and show a sensitive mechanism able to separate the components of the sample, we used the one-dimensional discontinuous SDS-PAGE under the following conditions: 120 minutes, 100 V and 25 mA. With the same samples were quantified the total proteins by the biuret method, determined by the methodology of the MFI measured turbidity and nitrates and nitrites by spectrophotometry. Research suggests that the reaction of nitrosating compounds (nitrates and nitrites) and nitronisáveis (proteins, amino acids and others) originate secondary substances, nitrous compounds. The zymogram revealed degradation of myofibrils in structures with molecular weight between 10 and 20 KDa. Protein content showed a decrease in the amount of protein in the samples roasted for 30 and 60 minutes from about 12.5%, and the determination of MFI was 42.93. The average nitrite in fresh samples, baked 60 minutes and 30 was 0.0001% (m / m), 0.0063% (w / w) and 0.0030% (w / w) respectively. The average nitrate found in fresh samples, baked 30 and 60 was 0.0020% (m / m), 0.00001% (m / m) and 0.00001% (m / m) respectively, both below 0.02% to 0.1% nitrite and nitrate as an upper limit set by law. Their absence or insignificant formation allows us to conclude that there is no relationship between protein degradation as evidenced by the change of myofibrillar zymogram, the MFI and the decrease of total proteins with a possible formation of secondary substances from nitrates and nitrites.
Keywords: Carvão vegetal; Nitrato; Nitrito; Sardinha (Peixe); Miofibrila; Nitrate; Nitrite; Fish myofibril; CIÊNCIA E TECNOLOGIA DE ALIMENTOS: CIÊNCIA DE ALIMENTOS